NONLINEAR FINITE ELEMENT ANALYSIS OF GASKETED FLANGE JOINT UNDER COMBINED LOADING CONDITIONS - MS. MANISHA H. SHENDKAR; PROF. AMOL. N. PATIL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Gasketed-flanged pipe joints have been widely used in industries for connecting pressure vessels and pipes. Joint strength and sealing strength are most important factors in the bolted flange joint. Most of the research work focused on the structural strength of the flange joint under internal pressure only. The research work does not consider the nonlinear behavior of gasket used in the flange coupling. The leakage and distortion of gaskets in bolted flange joints at high temperature is a well recognized problem and makes the problem more complex under combined application of internal pressure and temperature. To investigate the gasket sealing performance under the combined thermal and pressure load in the flange coupling, three different gasket materials with nonlinear behaviour will be considered for the application. A nonlinear finite element analysis of gasketed flange joint is carried out using ANSYS commercial software. The material nonlinearity for the Gasket and flange joint are considered to evaluate the deflection and stresses in the gasket. The suitable gasket material will be selected for the application. Finite element model is also verified with the available classical theories and experimental setup.